MiR‐182‐3p targets TRF2 and impairs tumor growth of triple‐negative breast cancer. Issue 1 (25th November 2022) - Dinami, Roberto; Pompili, Luca; Petti, Eleonora; Porru, Manuela; D'Angelo, Carmen; Di Vito, Serena; Rizzo, Angela; Campani, Virginia; De Rosa, Giuseppe; Bruna, Alejandra; Serra, Violeta; Mano, Miguel; et al.
Abstract: The telomeric repeat‐binding factor 2 (TRF2) is a telomere‐capping protein that plays a key role in the maintenance of telomere structure and function. It is highly expressed in different cancer types, and it contributes to cancer progression. To date, anti‐cancer strategies to target TRF2 remain a challenge. Here, we developed a miRNA‐based approach to reduce TRF2 expression. By performing a high‐throughput luciferase screening of 54 candidate miRNAs, we identified miR‐182‐3p as a specific and efficient post‐transcriptional regulator of TRF2. Ectopic expression of miR‐182‐3p drastically reduced TRF2 protein levels in a panel of telomerase‐ or alternative lengthening of telomeres (ALT)‐positive cancer cell lines. Moreover, miR‐182‐3p induced DNA damage at telomeric and pericentromeric sites, eventually leading to strong apoptosis activation. We also observed that treatment with lipid nanoparticles (LNPs) containing miR‐182‐3p impaired tumor growth in triple‐negative breast cancer (TNBC) models, including patient‐derived tumor xenografts (PDTXs), without affecting mouse survival or tissue function. Finally, LNPs‐miR‐182‐3p were able to cross the blood–brain barrier and reduce intracranial tumors representing a possible therapeutic option for metastatic brain lesions. Synopsis: A miRNA‐based strategy to inhibit the telomeric protein TRF2 was developed, which led to efficient decrease of triple negative breast cancer growth. miR‐182‐3p was identified as an efficient regulator of TRF2 expression in human cancer through high‐throughput miRNA luciferase screening. TRF2 inhibition by miR‐182‐3p induced DNA damage at telomeric and pericentromeric sites and consequent genomic instability. miR‐182‐3p limited the growth of Triple Negative Breast Cancer (TNBC) models by activating apoptosis. Lipid nanoparticles (LNPs) containing miR‐182‐3p reduced tumor volume in vivo in various TNBC models, including Olaparib‐resistant patient‐derived tumor xenografts. LNPs‐miR‐182‐3p crossed the blood brain barrier, showing therapeutic potential against brain metastasis. Abstract : A miRNA‐based strategy to inhibit the telomeric protein TRF2 was developed, which led to efficient decrease of triple negative breast cancer growth.